Penerapan Prinsip Good Corporate Governance di Bank Syariah Mandiri Cabang Sidoaro - Rahmawati A., Silviana; Hermawan, Sigit (Indonesian Journal Publisher, 2023)
This study aims to determine the implementation of the principles of good corporate governance implemented by Bank Syariah Mandiri Sidoarjo branch. This research uses a qualitative approach. The subjects of this research are the leadership (Branch Head), Operational Management and employees of Bank Syariah Mandiri Sidoarjo branch and Lecturers of Universitas Muhammadiyah Sidoarjo.. Sources of data obtained from interviews with informants or research subjects. Data were collected by means of interviews, observations, and documentation. Data analysis using qualitative methods. The results of the study found that Bank Syariah Mandiri (BSM) Sidoarjo Branch had implemented Good Corporate Governance (GCG) through the implementation of the principles of openness, accountability, responsibility, independence and fairness. The implementation of GCG at Bank Syariah Mandiri (BSM) Sidoarjo Branch has provided benefits in 1) Improved efficient, effective performance and continuity of an organization that contributes to the realization of the welfare of shareholders, employees and other stakeholders and is a good way out in overcoming organizational challenges in the future; 2) Increasing the legitimacy of organizations whose management is transparent, fair and accountable; 3) Recognition and protection of the rights and obligations of stakeholders; 4) An integrated approach in accordance with democratic principles, management and legal participation of the organization; 5) Control of conflicts of interest that arise between the owners of capital and management; 6) Reducing the cost of capital through positive signs or signals to investors.